Maintenance of plasma volume and serum sodium concentration despite body weight loss in ironman triathletes. - Hew-Butler, T; Collins, M; Bosch, A; Sharwood, K; Wilson, G; Armstrong, M; Jennings, C; Swart, J; Noakes, T (2007)
OBJECTIVE: To examine the relationship between body weight, plasma volume, and serum sodium concentration ([Na]) during prolonged endurance exercise. DESIGN: Observational field study. SETTINGS: 2000 South African Ironman Triathlon. PARTICIPANTS: 181 male triathletes competing in an Ironman triathlon. MAIN OUTCOME MEASURES: Body weight, plasma volume, and serum ([Na]) change from pre- to postrace. RESULTS: Significant body weight loss occurred (-4.9 +/- 1.7%; P < 0.0001), while both plasma volume (1.0 +/- 11.2%; P = 0.4: NS) and serum [Na] (0.6 +/- 2.4%; P < 0.001) increased from pre- to postrace. Blood volume (-0.6 +/- 6.6%) and red cell volume (-2.6 +/- 5.5%; P < 0.001) decreased in conjunction with the body weight loss. There was a strong correlation between blood and plasma volume change, both as a percentage, and absolute change in fluid volume (r = 0.9; P < 0.001). Body weight change was positively correlated with plasma volume change (r = -0.4; P < 0.001), but inversely correlated with serum [Na] change (r = -0.4; P < 0.001). Plasma volume change was not significantly correlated with serum [Na] change (r = 0.0; NS). Serum [Na] change was inversely correlated with both percentage of red cell volume change (r = -0.2; P < 0.05) and percentage body weight change (r = -0.4; P < 0.001). CONCLUSION: Plasma volume and serum [Na] were maintained in male Ironman triathletes, despite significant (5%) body weight loss during the course of the race. Body weight was not an accurate "absolute" surrogate of fluid balance homeostasis during prolonged endurance exercise. Clinicians should be warned against viewing these three regulatory parameters as interchangeable during an Ironman triathlon.